Common Fixed Point Theorems Using Subcompatible and Subsequentially Continuous Mappings on Partial Metric Spaces - Ravi, S.; Mallesh, B.; Srinivas, V. (Communications in Mathematics and Applications, 2023)
The purpose of this paper is to generate two common fixed point (CFP) theorems using subcompatible and reciprocally continuous and subsequentially continuous and compatible on partial metric spaces. Further, we extend our results with suitable examples.